Aplikasi Agen Hayati (Paenibacillus polymixa) terhadap Penekanan Penyakit Hawar Daun Bekteri Serta Hasil dan Pertumbuhan Padi Hitam (Oryza sativa)Var. Lokal - Endang Kantikowati; Ridwan Haris; Saiful Anwar (Paspalum: Jurnal Ilmiah Pertanian, 2018)
The Experiment  was aimed to assess influence of concentration and application of biological agent Paenibacillus polymixa to bacterial leaf blight disease and  black rice yields  (Oryza sativa L.) local varieties The research was conducted in P4S Al Mukhlis   Kiangroke Village, Bandung District, West Java. In December 2016 until April 2017. The experiment used a split-plot design with two factor : 3 application period (W) as the main plot and 4 concentration level (K) as the subplot, thus obtained 12 treatment combinations and each combination was repeated 3 times. Then obtained 36 plot of experiment. Factor I main plot (W) : W1 = morning application (10, 20, 30, 40, 50, 60, 70 days after planting), W2 = daytime (10, 20, 30, 40, 50, 60, 70 days after planting), W3 = afternoon application (10, 20, 30, 40, 50, 60, 70 days after planting) and factor II (K) : K1 = Control, K2 = 5 ml L-1, K3 = 10 ml L-1, K4 = 15 ml L-1. The result showed that the effect of concentration  and time of application of biological agent of Paenibacillus polymixa gave no significant effect on plant height, disease intensity, number of productive tillers, number of the dry grain harvest, number of unhulled grain per panicle, and weight of 1000 filled grains. There was an interaction between concentration and time of application of biological agent of Paenibacillus polymixa to bacterial leaf blight disease intensity at age of 95 DAP, treatment of K3 (10ml L-1) with W1 (morning application)   gave more resistance effect to bacterial leaf blight intensity.